2020
DOI: 10.1080/21663831.2020.1744758
|View full text |Cite
|
Sign up to set email alerts
|

Effect of surface grain boundary density on preosteoblast proliferation on titanium

Abstract: Studies since 2004 have shown that the cytocompatibility of ultrafine grain (UG) commercial purity (CP) titanium exceeds that of coarse grain (CG) CP titanium (Ti) by 30% to 20-fold. To isolate the factors affecting this large reported variability of CP titanium's cytocompatibility, discs of UG and CG titanium were fabricated with controlled texture and roughness. The discs were seeded with MC3T3-E1 pre-osteoblastic cells and cultured for 72 h. The proliferation of cells on polished UG-Ti exceeded unpolished C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…Because of the fact that the excellent physicochemical properties of a material’s surface reflect on the biological response, , roughness as well as wettability evaluation was carried out. The corresponding results are presented in Table and Figure S1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the fact that the excellent physicochemical properties of a material’s surface reflect on the biological response, , roughness as well as wettability evaluation was carried out. The corresponding results are presented in Table and Figure S1.…”
Section: Resultsmentioning
confidence: 99%
“…Commonly, the origin of superior biological behavior of the SPD-fabricated materials is related to the substantial differences in surface topography and its physicochemical properties, stemming from microstructural changes during the introduction of heavy strains into the volume of processed specimens. , So far, grain refinement, improved hydrophilicity and roughness, an augmented fraction of high-angle grain boundaries (HAGBs), as well as surface irregularities, in the form of nanodefects or nanogrooves, have been claimed to affect the cytocompatibility of SPD-processed titanium. ,, …”
Section: Introductionmentioning
confidence: 99%
“…Sandblasting the sample surfaces was found to produce a more favourable grain size and surface roughness, which promoted the attachment and proliferation of human gingival fibroblast cells. Recently, Lowe et al 47 studied the biocompatibility of UG and coarse-grain (CG) CP Ti with or without polishing treatment, and concluded that the UG and polished Ti could enhance the proliferation of MC3T3-E1 pre-osteoblastic cells. The average grain boundary length per surfaceattached cell was also identified as a new biophysical parameter that was correlated with cell proliferation.…”
Section: Mechanical Modification Methodsmentioning
confidence: 99%
“…The objective of this research project is to determine if RNA-seq can detect gene expression changes associated with the response of preosteoblasts during the osteoconduction stage on nanometrically smooth, compositionally identical substrates that differ by only their crystallographic structure. The substrates have an average grain size of 10.9 +/-7.3 μm (CG) and 0.24 +/-0.38 (UG), a 45-fold difference [31]. Characterization of mouse preosteoblasts growth on these discs included the development of a new bio-physical parameter, the ratio between the average grain boundary length (GBL) per unit area to the average cell contact area covered by cells (R GBL/cell ).…”
Section: Osteogenesis: Cell Proliferation and Differentiationmentioning
confidence: 99%
“…Details of disc fabrication and their physical properties are published elsewhere [31] and are available in the Compendium of Biomaterials Transcriptomics (cBiT) [32]. Briefly, CG-Ti rods were obtained from the Carpenter Technology Corporation (Reading, Pennsylvania), UG rods were bulk nanostructured via C-ECAP, applying at least four passes with interpass billet rotations of 90˚following route B c at 200˚C to 350˚C.…”
Section: Ti Disc Preparationmentioning
confidence: 99%